Young peoples' lived experiences of multidisciplinary mental health assessment in an intensive day program. (June 2022) - Aitchison, Kate A; McFerran, Katrina S
Objective: We aimed to explore young peoples' lived experiences of multidisciplinary mental health assessment in an intensive mental health day program. Method: Interpretative phenomenological analysis (IPA) was applied to data from semi-structured interviews with six males, aged 13–16 years. Member-checking interviews were conducted to ensure the trustworthiness of findings. Results: Analysis revealed three themes, 'therapy fatigue', '360 supports' and 'experiential assessment'. Participants had either attended many years of psychological therapy without significant change or had failed to engage with therapy. Participants' attitudes changed at the day program with intensive support and their own determination. Participants valued experiential elements of assessment such as music therapy and art therapy which helped them understand the service, get to know others and experience positive emotions. Conclusions: Unsuccessful psychological treatment can leave young people feeling jaded and reluctant to engage with services. The potential for iatrogenic harm should be monitored and alternative approaches, such as intensive, multidisciplinary treatment including music therapy and art therapy considered to help young people overcome therapy fatigue, regain hope and reengage with mental health services.